ECONOMIC ASPECTS OF SHEEP FARMING ON THE FAMILY FARM MODELS IN THE HILLY-MOUNTAIN REGIONS OF SERBIA - Popović, Nikola (Economics of Agriculture, 2018)
The hilly-mountain villages are important factor in food production and rural development of Serbia. The sheep production is in the fourth place of importance among branches of livestock production in Serbia, behind the cattle, pig and poultry productions. The aim of the paper is to analyze economic indicators of the sheep farming on family farms in Serbian hilly-mountain regions on the basis of 4 models which differ in intensity of crop and sheep production and to consider possibilities for improvement. The analysis has been done on the basis of data collected on 30 family farms. The economic indicators have been calculated on the basis of Direct costing calculation method and gross margins. The results have shown that production of lamb meat and sheep cheese represent the main source of the family farms income in the hilly-mountain regions. The Model D with intensive crop and sheep production obtained the best economic results.